Systemic Trans-Splicing Adeno-Associated Viral Delivery Efficiently Transduces the Heart of Adult mdx Mouse, a Model for Duchenne Muscular Dystrophy - Ghosh, Arkasubhra (Mary Ann Liebert, Inc., 2009)
Trans-splicing adeno-associated viral (tsAAV) vectors hold great promise for delivering large therapeutic genes. One potential application is in the treatment of Duchenne muscular dystrophy (DMD). In this case, it is necessary to transduce whole body muscle. We demonstrated body-wide AAV-9 tsAAV transduction in normal neonatal mice. However, it was not clear whether such an approach would work in diseased mice. In this study we delivered the AAV-9 alkaline phosphatase (AP) tsAAV vector (3 × 10(12) vector genome particles per vector per mouse, tail vein injection) to 2-month-old mdx mice, the most widely used DMD model. Four months later, we observed widespread AP expression in the heart. It reached the same level as we have seen in normal neonatal puppy. Interestingly, myocardial transduction correlated with β-myosin heavy chain expression but not with LamR, the putative AAV-9 receptor. AP expression was also detected in various skeletal muscles but at levels much lower than in normal newborn mice. Despite the existing inflammatory milieu, we did not see any appreciable increase in CD4(+) and CD8(+) T cells and macrophages in striated muscles after systemic tsAAV infection. In summary, our results have paved the way for tsAAV-mediated gene therapy for Duchenne cardiomyopathy.